Lettre de Monsieur le marquis de Bonniuet escrite au roy. - Bonnivet, Henri-Marc de Gouffier, Marquis de, 1586-1645 ([France?] : [Publisher not identified], 1615)
"Bonnivet, implicated in the murder of Henry IV, appealed to many different people to help him in his efforts to return to his homeland from his place of refuge in England. Here he appeals to Condé and the other princes"--French Political Pamphlets Digital Collection, Brigham Young University.
Variant of Lindsay, R.O. French political pamphlets, 1547-1648, entry 3227.
Page 7 (A4r) misnumbered 6.
Signatures: A⁴ (last page blank).
Also available via the World Wide Web.
Mode of access: Internet.
RBC copy: Disbound.
Keywords: Condé, Henri II de Bourbon, -- prince de, -- 1588-1646.; Louis -- XIII, -- King of France, -- 1601-1643.; 1610-1643; France; France -- Politics and government -- 1610-1643.; France -- History -- Louis XIII, 1610-1643 -- Pamphlets; Pamphlets -- France -- Seventeenth century (dates CE).; History